1997
DOI: 10.1007/s11738-997-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of faba bean plants to soil and foliar N application and K nutrition

Abstract: The effect of different rates and methods of fertilizer nitrogen application and potassium nutrition on the root nodule t'ormation of faba bean plants vat. Nadwiglafiski and on their nitrogenase activity was studied. It was found that fertilizer N depressed the nodule formation and nitrogenasc activity, but inhibitory effect of N was smaller when it was supplied to the leaves instead to the soil. Plants growing at higher K level were in a position allowing on better development of nodules and consequently high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The highest number of nodules was obtained at N 1 (30 N kg/ha) level. Our results are in line with the findings of Wojcieska and Kocon (1997), Achakzai (2007) and Oladiran et al (2012).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The highest number of nodules was obtained at N 1 (30 N kg/ha) level. Our results are in line with the findings of Wojcieska and Kocon (1997), Achakzai (2007) and Oladiran et al (2012).…”
Section: Resultssupporting
confidence: 94%
“…In terms of nodule weight/plant, the highest weight (0.42 g) was obtained at N 1 (30 N kg/ha) level. Wojcieska and Kocon (1997), Achakzai (2007) and Oladiran et al (2012) also obtained similar results.…”
Section: Resultsmentioning
confidence: 60%
“…However, N fertilization may result in a reduction of nodulation and N 2 fixation (Peoples et al 2002;Stern 1993;Van Kessel and Hartley 2000). The inhibitory effect of N fertilization on nodulation and N 2 fixation of faba bean has been found under both greenhouse and field conditions (Fan et al 2006;Hardarson et al 1991;Richards and Soper 1979;Wojcieska and Kocoñ 1997). After analyzing 637 data sets on soybean (Glycine max L.) from 108 field studies published between 1966 and 2006, Salvagiotti et al (2008) found a negative exponential relationship between the nitrogen derived from air (Ndfa) and Nfertilizer rate and that %Ndfa decreases with increasing inputs of N fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Lignite is used as the carrier in this commercial inoculant. Despite knowing that K deficiency can occur in the region [6] and that abundant K can positively affect the nodulation of faba bean [19], we chose not to use K fertilisation. Potassium is not included in the blanket fertiliser recommendation in the area, and we wanted to make an experiment as close as possible to the practical farming practices.…”
Section: Experimental Material Treatments Design and Proceduresmentioning
confidence: 99%